Analysis of some variable kinematical to triple jump world champions for the World Championships in 2013 - Razzaq, Z. A. S. A.; Mutashar, S. A.; Al Shammari, A. R. (Journal of Human Sport & Exercise, 2019)
To achieve the completion of any athlete requires knowledge and mechanical factors impacts on it and the lack of achievement is due to the neglect of some important parameters in athletic training specialist. This achievement is the process of the most adverse factors related the sports training. Motor analysis is utilized to evaluate the performance actions level and mathematical skills while players exactly, and in which you can find the mount of variables kinematical and evaluated via parameters kinematical model to sense the strengths and weaknesses in the player`s performance in comparison to players, which assist in improving this performance. The contest triple jump competitions force fast they require a great deal of power mixed with speed also requires the control of an integrated performance requirements of physical and skill and also requires a high speed when you approach with a balance of high and balanced force for the feet together and are similar to the effectiveness of the long jump.